Rezension von: Kirchgässner, Bernhard; Scholz, Günter (Hrsg.), Stadt und Krieg - Fritz, Gerhard (Württembergisch Franken, 1992)
Stadt und Krieg / hrsg. von Bernhard Kirchgässner u. Günter Scholz. - Sigmaringen: Thorbecke, 1989. - 294 S. (Stadt in der Geschichte; 15)